Digital Transformation: The Role of the Big Five Personality Traits - Pradana, Bartolomeus Galih Visnhu; Mayasari, Agatha (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
This study aimed to investigate the role of the big five personality qualities in mediating the relationship between digital transformation and team member performance. The world of education is feeling the effects of digital transformation, a significant phenomenon that the industry cannot avoid. The presence of digital transformation causes modifications in traditional operations to be digitized. This shift in change affects team member performance. This survey included 83 elementary to middle school teachers and education staff from the Marsudirini Foundation's Yogyakarta branch. The hypothesis was tested using PLS-SEM in this study, which used a mixed method. The hypothesis testing results revealed that digital transformation has a beneficial effect on team member performance. When the role of moderation is tested, it is discovered that extraversion and neuroticism personality types do not significantly affect the relationship between digital transformation and team member performance. Meanwhile, as moderating variables, agreeableness, conscientiousness, and openness personality types strongly negatively affect the association between digital transformation and team member performance. Informant interviews corroborate the survey results, highlighting the insignificant effect of extraversion and neuroticism personality types.